2021
DOI: 10.1097/mao.0000000000003235
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Transcanal Endoscopic Ear Surgery to Post-Auricular Microscope-Guided Surgery in Pediatric Ossiculoplasty: Hearing Outcomes and Post-Operative Pain

Abstract: Objective: This study compares post-operative hearing outcomes and morbidity after pediatric total ossicular replacement prosthesis (TORP) ossiculoplasty with transcanal totally endoscopic ear surgery (TEES) versus a post-auricular microscope-guided (PAM) approach. Patients: Forty-four children who underwent ossiculoplasty with titanium TORP after previous cholesteatoma surgery Intervention: Ossiculoplasty using TEES or PAM approach. Main outcome measures: Hearing outcome after ossiculoplasty was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…To our knowledge, our study is the largest to primarily investigate the results of endoscope-assisted total ossiculoplasty. In addition, our follow-up is longer than previously described in literature (1–3). Das et al (1) described significantly better hearing results 1 month after endoscope-assisted ossiculoplasty in comparison to microscope-assisted ossiculoplasty.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…To our knowledge, our study is the largest to primarily investigate the results of endoscope-assisted total ossiculoplasty. In addition, our follow-up is longer than previously described in literature (1–3). Das et al (1) described significantly better hearing results 1 month after endoscope-assisted ossiculoplasty in comparison to microscope-assisted ossiculoplasty.…”
Section: Discussionmentioning
confidence: 81%
“…Yet, at 6 months after surgery both methods were shown to have comparable audiologic outcomes. Yawn et al and Kwinter et al ( 2 , 3 ) state that audiologic results of endoscope-assisted and microscope-assisted ossiculoplasty are equal. Short-term endoscopic results from our study are comparable to those in literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who undergo endoscopic ear surgery have reduced postoperative pain, as well as improved disease-specific quality of life and improved general anxiety [13]. Pain scores are significantly higher in children undergoing postauricular surgery than in children undergoing totally endoscopic surgery, with children undergoing endoscopic surgery often reporting pain scores of 0 on the visual analogue scale [12]. These results are supported by a recent systematic review and meta-analysis of 11 studies, which confirmed that endoscopic ear surgery is associated with significantly less postoperative pain than microscopic ear surgery [14].…”
Section: Endoscopic Ear Surgerymentioning
confidence: 99%
“…Endoscopic ear surgery has also been associated with reduced healthcare expenditures [9] and reduced operative time [12]. In a prospective case series of patients undergoing cholesteatoma surgery, ears were checked with an endoscope, intraoperatively, at the completion of microscopic dissection.…”
Section: Endoscopic Ear Surgerymentioning
confidence: 99%